IDENTIFIKASI SEKTOR BASIS DAN SEKTOR NON-BASIS MENGGUNAKAN METODE LOCATION QUOTIENT (LQ), SHIFT SHARE (SS), DAN TIPOLOGI KLASSEN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SERANG - Laela Faiqotul Himmah; Marseto; Anisa Fitria Utami (Universitas Nias Raya, 2025)
This study aims to identify the base and non-base sectors in the economy of Serang Regency for the period 2014–2023 and analyze changes in the economic structure of the region. The data used is secondary data in the form of Gross Domestic of Banten Province and Serang Regency. The methods use dare location quotient (LQ), shift share, Klassen typology, and simple linear regression. The results of the analysis show that during the research period there were four consistent base sectors, namely agriculture, forestry and fisheries; manufacturing; government administration, defense and mandatory social security; and education services. These sectors have comparative and competitive advantages that are the main drivers of regional economic growth. Based on Klassen's typology, Serang Regency is classified as a rapidly advanced and developing region. The results of this study are expected to be taken into consideration by local governments in planning for sustainable economic development. The results of the regression test show that the basic sectors have a significant effect on economic growth, while the non-basic sectors do not have a significant effect.